Optimising tropical fruit juice quality using thermosonication-assisted extraction via blocked face-centered composite design - Abdullah, Norazlin; Chin, Nyuk Ling (MDPI, 2020)
Extraction of tropical fruit juice using simple, efficient, and environmentally friendly technologies is gaining importance to produce high quality juices. Juice from pink-fleshed guava, pink-fleshed pomelo, and soursop was extracted using direct and indirect thermosonication methods by varying intensity, time, and temperature, and compared to those extracted using water bath incubation. Improvised models of juice yield, ascorbic acid, and total soluble solids responses were generated by eliminating insignificant model terms of the factors in full quadratic model using backward eliminating procedure. Main effects, 3D, or 4D plots for each response were developed based on factors that influenced the response. Results showed that the best extraction method for guava and pomelo juices were within indirect thermosonication method of 1 kW, 55 ◦C and 30 min, and 2.5 kW, 54 ◦C and 23 min, respectively. Direct thermosonication method at 10% amplitude, 55 ◦C for 2 to 10 min was more suitable for soursop juice. Thermosonicated extraction of tropical fruit juice can improve its juice yield, ascorbic acid content, and total soluble solids content.